PP58 SARS-CoV-2: A Rapid Review Of The Transmission Risk From Vaccinated Populations. (23rd December 2022) - Barrate, Sasha; Elston, Lauren; McDermott, Katie; Washington, Jenni; Hasler, Elise; Jarrom, David; Bowles, Charlotte; Tom Winfield, Jessica Williams; Myles, Susan
Abstract : Introduction: Since the vaccine roll out, research has focused on vaccine safety and efficacy, with large clinical trials confirming that vaccines are generally effective against symptomatic COVID-19 infection. However, breakthrough infections can still occur, and the effectiveness of vaccines against transmission from infected vaccinated people to susceptible contacts is unclear. Health Technology Wales (HTW) collaborated with the Wales COVID-19 Evidence Centre to identify and examine evidence on the transmission risk of SARS-CoV-2 from vaccinated people to unvaccinated or vaccinated people. Methods: We conducted a systematic literature search for evidence on vaccinated people exposed to SARS-CoV-2 in any setting. Outcome measures included transmission rate, cycle threshold (Ct) values and viral load. We identified a rapid review by the University of Calgary that was the main source of our outcome data. Nine studies published following the rapid review were also identified and included. Results: In total, 35 studies were included in this review: one randomized controlled trial (RCT), one post-hoc analysis of an RCT, 13 prospective cohort studies, 16 retrospective cohort studies and four case control studies. All studies reported a reduction in transmission of the B.1.1.7 (Alpha) variant from partial and fully vaccinated individuals. More recent evidence is uncertain on the effects of vaccination on transmission of the B.1.617.2 (Delta) variant. Overall, vaccine effectiveness in reducing transmission appears to increase with full vaccination, compared with partial vaccination. Most of the direct evidence is limited to transmission in household settings therefore, there is a gap in the evidence on risk of transmission in other settings. One UK study found protection against onward transmission waned within 3 months post second vaccination. Conclusions: Early findings that focused on the alpha variant, showed a reduction in transmission from vaccinated people. There is limited evidence on the effectiveness of vaccination on transmission of the Delta variant, therefore alternative preventative measures to reduce transmission may still be required.